Disfunctions of Bureaucracy dan Mal-Administrasi Pemerintah dalam Pengelolaan Sampah di Kabupaten Sinjai - Syahril Syahril; Rasyid Thaha; A.M. Rusli (Universitas Medan Area, 2021)
This paper aims to examine the bureaucratic pathology of waste management in Sinjai Regency as well as the government's efforts to deal with the pathology that occurs. The type of research used in this research is qualitative which will provide a factual picture of the research objectives. The results showed: the form of pathology found, namely Disfunctions of bureaucracy and Mal-Administration of the government structurally must implement waste management policies, namely the facilities and infrastructure must comply with regulations and the performance of officers who should run according to their duties and functions Efforts that must be made by the government, namely guidance and supervision of the regulations that have been set and contained in the regional regulations of Sinjain Regency number 10 of 2017 must be maximized. The efforts made by the Sinjai Regency government in overcoming the form of bureaucratic pathology faced in the implementation of hygiene policies, namely the lack of guidance, such as education on awareness of cleanliness to the public and supervision of people who are still littering in any place carried out at every level of government starting from the Regency level, the District level to the village level.